Link Between m6A Modification and Cancers - Liu, Zhen-Xian; Li, Li-Man; Sun, Hui-Lung; Liu, Song-Mei (Frontiers in Bioengineering and Biotechnology, 2018)
N6-methyladenosine (m6A) epitranscriptional modification has recently gained much attention. Through the development of m6A sequencing, the molecular mechanism and importance of m6A have been revealed. m6A is the most abundant internal modification in higher eukaryotic mRNAs, which plays crucial roles in mRNA metabolism and multiple biological processes. In this review, we introduce the characteristics of m6A regulators, including "writers" that create m6A mark, "erasers" that show demethylation activity and "readers" that decode m6A modification to govern the fate of modified transcripts. Moreover, we highlight the roles of m6A modification in several common cancers, including solid and non-solid tumors. The regulators of m6A exert enormous functions in cancer development, such as proliferation, migration and invasion. Especially, with the underlying mechanisms being uncovered, m6A and its regulators are expected to be the targets for the diagnosis and treatment of cancers. Key words: m6A, mRNA, Cancers